BIBLIOMETRIC ANALYSIS OF THE FOOD ESTATE PROGRAM: ENVIRONMENTAL SUSTAINABILITY, AGRARIAN CONFLICTS, AND POLICY IMPLICATIONS FOR INDONESIA’S FOOD SECURITY - M. Rasda; Mukmin Muhammad (Meraja journal, 2025)
[Full Paper] to pdf Copyright (c) 2025 Meraja journal